Doxorubicin-loaded PEG-CdTe QDs conjugated with anti-CXCR4 mAbs: a novel delivery system for extramedullary multiple myeloma treatment - Dangui Chen; Fei Chen; Jia Lu; Lihong Wang; Fusheng Yao; Haitao Xu (Journal of Materials Science: Materials in Medicine)
Abstract Extramedullary multiple myeloma (EMM) is defined as the presence of plasma cells outside the bone marrow of multiple myeloma patients, and its prognosis is poor. High-dose chemotherapy with autologous stem cell transplantation, as a good option on early lines of therapy, has retained the survival benefit of youny EMM patients, but is intolerant for the majority of old patients because of drug cytotoxicity. To essentially address the intolerance above, we designed a CXCR4-PEG-CdTe-DOX (where CXCR4: chemokine receptor 4; PEG-CdTe: polyethylene glycol-modified cadmium telluride; DOX:doxorubicin) nanoplatform. First, CXCR4 is highly expressed in extramedullary plasma cells. Second, PEG-CdTe a drug carrier that controls drug release, can reduce adverse reactions, prolong drug (e.g, DOX) circulation time in the body, and form a targeting carrier after connecting antibodies. In vitro experiments showed CXCR4-PEG-CdTe-DOX facilitated intracellular drug accumulation through active CXCR4 targeting and released DOX into the microenvironment in a pH-controlled manner, enhancing the therapeutic efficacy and apoptosis rate of myeloma cells (U266). Therefore, targeted chemotherapy mediated by CXCR4-PEG-CdTe-DOX is a promising option for EMM treatment. Graphical abstract Figure 1 Action mechanism of drug delivery pathway: CXCR4-PEG-CdTe-DOX nanocomplex can be targeted and close to MM cell membranes, effectively transport DOX into MM cells, and promote MM cell apoptosis.